2021
DOI: 10.1186/s42523-021-00086-4
|View full text |Cite
|
Sign up to set email alerts
|

Fish predation on corals promotes the dispersal of coral symbionts

Abstract: Background The microbiomes of foundation (habitat-forming) species such as corals and sponges underpin the biodiversity, productivity, and stability of ecosystems. Consumers shape communities of foundation species through trophic interactions, but the role of consumers in dispersing the microbiomes of such species is rarely examined. For example, stony corals rely on a nutritional symbiosis with single-celled endosymbiotic dinoflagellates (family Symbiodiniaceae) to construct reefs. Most corals… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 68 publications
1
15
0
Order By: Relevance
“…Symbiodiniaceae type profiles were largely made up of C3 variants (Cladocopium genus) along with a few corals hosting A1 and A3 (Symbiodinium genus) (figure 2d-f; electronic supplementary material, figure S7), consistent with compositions found by Putnam et al [57]. Interestingly, Howe-Kerr et al [58] found higher frequencies of Symbiodinium and Durusdinium genera than Cladocopium in their 2019 collections, despite their sampling from adjacent reefs in Mo'orea. This may reflect a shift in A. hyacinthus Symbiodiniaceae communities due to climate change stressors, given that collections from Putnam et al [57] and our study occurred prior to 2014 and a devastating bleaching event occurred in Mo'orea in 2019.…”
Section: (B) Higher Diversity Symbiodiniaceae Communities In Fore Reef Environmentssupporting
confidence: 79%
“…Symbiodiniaceae type profiles were largely made up of C3 variants (Cladocopium genus) along with a few corals hosting A1 and A3 (Symbiodinium genus) (figure 2d-f; electronic supplementary material, figure S7), consistent with compositions found by Putnam et al [57]. Interestingly, Howe-Kerr et al [58] found higher frequencies of Symbiodinium and Durusdinium genera than Cladocopium in their 2019 collections, despite their sampling from adjacent reefs in Mo'orea. This may reflect a shift in A. hyacinthus Symbiodiniaceae communities due to climate change stressors, given that collections from Putnam et al [57] and our study occurred prior to 2014 and a devastating bleaching event occurred in Mo'orea in 2019.…”
Section: (B) Higher Diversity Symbiodiniaceae Communities In Fore Reef Environmentssupporting
confidence: 79%
“…This is of relevance because interhost dispersal of bacteria is not a rare phenomenon. Transmission of microbes from one individual to another one in a shared environment has been documented previously for aquatic systems, as exemplified in corals ( Grupstra et al, 2021 ), zebrafish ( Burns et al, 2017 ), microcosm ( Shen et al, 2018 ), and zooplankton ( Grossart et al, 2010 ). Moreover, co-housing of mice has a profound effect on their gut microbiome ( Caruso et al, 2019 ; Robertson et al, 2019 ).…”
Section: Discussionmentioning
confidence: 74%
“…The authors noted that egesta released by H. crispa were consumed by symbiotic anemonefish ( Alan Verde, Cleveland & Lee, 2015 ). It is not known if other animals consume Aiptasia egesta in nature, but if so, they may aid in algal dispersal, as algae often survive digestion ( Parker, 1984 ; Grupstra et al, 2021 ; Grupstra et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%